Lithology and features of polymineral alluvium separation, on the example of rivers of Ukraine - Беліцька, М. В.; Іванченко, В. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The river network is part of modern geological environment. It reflects the dynamics of natural processes and the impact of technogenic factors. Changes in the ecological condition of the environment are necessitated by the study and management of alluvium accumulated in the river network in Ukraine. Some 100 samples of alluvium in the rivers Dnieper, Pivdenniy Bug, Ingul, Ingulets and others have been studied. Optical and electron microscopy, lithological and technological researches have been used. Light fraction consists of quartz, carbonates (including organic), feldspar, kaolinite predominates in a fine grade alluvium. Heavy fraction contains almandine, ilmenite, zircon, monazite, to a lesser extent apatite, rutile. Sometimes there is gold, silver, diamonds and other rare minerals. Available particles of metallic iron, bronze, steel sludge, slag, refractories, glass and ore balls are the indicators of the anthropogenic pollution of environment. Dry separation of alluvium has been used in the laboratory. As a result we obtained concentrates of heavy minerals: garnet, ilmenite, monazite, minerals of iron. With the tailings of separation quartz, marshalit, gypsum, carbonates, clay was obtained. Separation methods of natural and contaminated sediments were different, because of the presence of industrial waste in the composition of contaminated alluvium. Researches are confirmed by a polygenic (natural and man-made) formation of high concentrations of heavy minerals in the river alluvium. Extraction of heavy minerals also has ecological significance, since it leads to the clearing of rivers from industrial wastes.